PENERAPAN MEDIA ANIMASI DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPS KELAS IV MIN 7 ACEH BARAT - Iba Elisa; Muhammad Iqbal (Program Studi Manajemen Pendidikan Islam, 2025)
The learning outcomes of fourth-grade students of MIN 7 West Aceh in the social studies learning process, especially on the theme of caring for living things in madrasas, tend to be low. Students are less interested in the learning activities taught, so that it causes the learning outcomes to not reach the optimal standard. The purpose of this study was to determine the activities of teachers and students in the application of animation media to improve student learning outcomes in fourth-grade social studies lessons at MIN 7 West Aceh and to determine the application of animation media to improve student learning outcomes in fourth-grade social studies lessons at MIN 7 West Aceh. This type of research is Classroom Action Research (CAR) with all 16 fourth-grade students of MIN 7 West Aceh as subjects. The data collection techniques used were observation and tests. The data analysis technique used descriptive analysis. The results of this study indicate that the application of animation media in social studies subjects on the theme of caring for living things in fourth-grade MIN 7 West Aceh can increase the activities of teachers and students. Student learning interest, which is characterized by an increase in student learning outcomes through the application of animation media, has increased, this can be seen from student learning outcomes starting from the Pretest, Posttest cycle I, to Posttest cycle II. It can be seen from the average student pretest score of 55, increasing in the final test of cycle I the average student score to 66.9 and in cycle II the average score increased again to 78.1. Likewise, in terms of completeness, there was also an increase from cycle I to cycle II, namely 56.3% rising to 81.3%.